Pugs From Planet X : Max Meow # 3 - Gallagher, John, 1967- (New York : Random House Children's Books, 2021)
"Pugs from outer space want to steal the meatball that gave Max Meow his superpowers, and it's up to Max and Mindy to stop them"--.
Ages 7-10.
Keywords: Superheroes -- Fiction; Pug -- Fiction; Ability -- Fiction; Cats -- Fiction; Dogs -- Fiction; Graphic novels